Physiological and behavioral responses in offspring mice following maternal exposure to sulfamonomethoxine during pregnancy. (15th June 2016) - Zhang, Qiang; Zhang, Dan; Ye, Kui; Liu, Kaiyong; Sheng, Jie; Liu, Yehao; Hu, Chunqiu; Ruan, Liang; Li, Li; Tao, Fangbiao
Highlights: Pregnant SMM exposure enhanced blood glucose level in offspring mice. Pregnant SMM exposure induced anxiety in mice offspring late in life. SMM exposure impaired the spatial memory more seriously in male offspring. Prgnant SMM exposure reduced BH4 and BDNF levels in mice offspring early in life. Abstract: Sulfamonomethoxine (SMM), a veterinary antibiotic, is widely used in China. However, the impacts of maternal SMM exposure on neurobehavioral development in early life remain little known. In this study, we investigated the effects of maternal SMM exposure during pregnancy on behavioral and physiological responses in offspring mice. Pregnant mice were randomly divided into three SMM-treated groups, namely low-(10 mg/kg/day), medium-(50 mg/kg/day), and high-dose (200 mg/kg/day), and a control group. The pregnant mice in the SMM-treated groups received SMM by gavage daily from gestational day 1–18, whereas those in the control received normal saline. On postnatal day (PND) 50, spatial memory was assessed using the Morris water maze test, and anxiety was measured using the elevated plus-maze and open field tests. The results showed significantly increased blood glucose in pups whose mothers received a high SMM dose. In addition, maternal SMM exposure increased anxiety-related activities among the offspring; spatial learning and memory were impaired more severely in the male offspring. The contents of tetrahydrobiopterin (BH4 ) and brain-derived neurotrophic factors (BDNF) on PND 22 were significantly reduced in the male offspring of the high-dose group compared with the controls. These findings indicate that SMM may be identified as a risk factor for cognitive and behavioral development on the basis of gender and that it may be associated with diminished BH4 and BDNF levels early in life.